Effect of bicycle racing saddle design on transcutaneous penile oxygen pressure - Cohen, J. D.; Gross, M. T. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: To determine the reliability of monitoring penile transcutaneous oxygen (tpO2) during cycling, and to assess the influence of seat design and cycling position on tpO2. Methods: Experimental design: repeated measures analysis of the effects of seat design and riding position on tpO2 values. Participants: 31 male cyclists between the ages of 20 and 50 years participated. Subject inclusion criteria were: averaged >=80 miles of road bicycling per week during the 2 months prior to enrollment in this study; no history of vascular disease, diabetes, or sexual dysfunction; and had an erection within 15 days prior to study. Measures: mean tpO2 values were calculated for seated and standing positions using 3 current bicycle seat designs. Results: Test-retest reliability for seated cycling tpO2 values had an ICC (3,1) of 0.76 and mean absolute difference of 5.1 mmHg. Test-retest reliability for standing cycling tpO2 values had an ICC(3,1) of 0.88 and mean absolute difference of 7.23 mmHg. No interaction effect occurred between seat design and position. Seat design had no significant effect on tpO2 values. Seated cycling significantly reduced tpO2 levels compared with standing cycling (P<0.05). Mean percent decreases in tpO2 from standing to seated cycling were; Vetta® 76%, Terry® 73%, and Specialized® 62%. Conclusion: The data suggest that penile tpO2 monitoring is reliable for use during cycling studies. None of the seats exhibited any significant ability to spare penile tpO2. The implications of decreased penile tpO2 over different time intervals on penile physiology remain to be investigated.